Validation of the REGARDS Severe Sepsis Risk Score. - Wang, Henry E; Donnelly, John P; Yende, Sachin; Levitan, Emily B; Shapiro, Nathan I; Dai, Yuling; Zhao, Hong; Heiss, Gerardo; Odden, Michelle; Newman, Anne; Safford, Monika (J Clin Med, 2018)
There are no validated systems for characterizing long-term risk of severe sepsis in community-dwelling adults. We tested the ability of the REasons for Geographic and Racial Differences in Stroke-Severe Sepsis Risk Score (REGARDS-SSRS) to predict 10-year severe sepsis risk in separate cohorts of community-dwelling adults. We internally tested the REGARDS-SSRS on the REGARDS-Medicare subcohort. We then externally validated the REGARDS-SSRS using (1) the Cardiovascular Health Study (CHS) and (2) the Atherosclerosis Risk in Communities (ARIC) cohorts. Participants included community-dwelling adults: REGARDS-Medicare, age ≥65 years, = 9522; CHS, age ≥65 years, = 5888; ARIC, age 45⁻64 years, = 11,584. The primary exposure was 10-year severe sepsis risk, predicted by the REGARDS-SSRS from participant sociodemographics, health behaviors, chronic medical conditions and select biomarkers. The primary outcome was first severe sepsis hospitalizations, defined as the concurrent presence of ICD-9 discharge diagnoses for a serious infection and organ dysfunction. Median SSRS in the cohorts were: REGARDS-Medicare 11 points (IQR 7⁻16), CHS 10 (IQR 6⁻15), ARIC 7 (IQR 5⁻10). Severe sepsis incidence rates were: REGARDS-Medicare 30.7 per 1000 person-years (95% CI: 29.2⁻32.2); CHS 11.9 (10.9⁻12.9); ARIC 6.8 (6.3⁻7.3). SSRS discrimination for first severe sepsis events were: REGARDS-Medicare C-statistic 0.704 (95% CI: 0.691⁻0.718), CHS 0.696 (0.675⁻0.716), ARIC 0.697 (0.677⁻0.716). The REGARDS-SRSS may potentially play a role in identifying community-dwelling adults at high severe sepsis risk.